2018
DOI: 10.2151/jmsj.2018-006
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Resolution Numerical Weather Prediction with a Large Domain Using the K Computer: A Case Study of the Izu Oshima Heavy Rainfall Event on October 15-16, 2013

Abstract: An intense rainband associated with Typhoon 1326 (Wipha) induced a fatal debris flow on Izu Oshima, Japan, on October 15 -16, 2013. This rainband formed along a local front between the southeasterly humid warm air around the typhoon and the northeasterly cold air from the Kanto Plain. In this paper, the Japan Meteorological Agency Nonhydrostatic Model was optimized for the "K computer", and ultra-high-resolution (500 -250 m grid spacing) numerical simulations of the rainband with a large domain were conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…The total precipitation is larger in TOPO1km than in TOPO100m in all three cases, suggesting that the presence of submesoscale topography reduces precipitation. This contrasts with the results of Oizumi et al (2018) and Takemi (2018); when the mechanical effect of topography was dominant, precipitation was enhanced. The difference in total precipitation is mainly due to intense precipitation over 1 mm h 21 .…”
Section: A Statistical Characteristicscontrasting
confidence: 96%
See 1 more Smart Citation
“…The total precipitation is larger in TOPO1km than in TOPO100m in all three cases, suggesting that the presence of submesoscale topography reduces precipitation. This contrasts with the results of Oizumi et al (2018) and Takemi (2018); when the mechanical effect of topography was dominant, precipitation was enhanced. The difference in total precipitation is mainly due to intense precipitation over 1 mm h 21 .…”
Section: A Statistical Characteristicscontrasting
confidence: 96%
“…A few studies have investigated the influence of submesoscale topography on precipitation with realistic topography. Numerical simulations using a terrain height dataset with subkilometer resolution enhanced the simulated precipitation of a coastal front associated with a typhoon (Oizumi et al 2018) and a stationary linear-shaped convective system under the baiu front 1 (Takemi 2018). Under these circumstances, submesoscale topography is thought to enhance the mechanical effects of largerscale topography on precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…For wind representations, Oku et al (2010), Takemi et al (2010), and Takemi (2013) demonstrated that accurate representations of fine topographical features improve the representations of extreme winds in complex terrain. For rainfall, Takemi (2010) and Oizumi et al (2018) showed that the simulation with finer terrains reproduced stronger rains. However, there are few studies that examined how topographical representations affect quantitative simulations of heavy rainfalls.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that a senjo-kousuitai event observed in Fukui Prefecture in 2004 could not be reproduced due to uncertainty in the initial lowlevel wind conditions. Oizumi et al (2018) investigated the dependence of the reproducibility of a senjo-kousuitai event observed across Izu-Oshima Island in 2013 (see Fig. 1a) on the horizontal resolution (5 km, 2 km, 500 m, and 250 m) and planetary boundary schemes.…”
Section: Introductionmentioning
confidence: 99%